Complete genome sequence and comparative analysis of a Vibrio vulnificus strain isolated from a clinical patient - Wu, Fei; Zhang, Tingting; Wu, Qimin; Li, Xue; Zhang, Miaomiao; Luo, Xi; Zhang, Yiquan; Lu, Renfei (Frontiers in Microbiology, 2023)
Vibrio vulnificus is an opportunistic, global pathogen that naturally inhabits sea water and is responsible for most vibriosis-related deaths. We investigated the genetic characteristics of V. vulnificus isolated from the clinical blood culture specimen of a patient with hepatitis B virus cirrhosis in 2018 (named as V. vulnificus VV2018) by whole genome sequencing (WGS). VV2018 belonged to a novel sequencing type 620 (ST620) and comprised two circular chromosomes, containing 4,389 potential coding sequences (CDSs) and 152 RNA genes. The phylogenetic tree of single nucleotide polymorphisms (SNPs) using 26 representative genomes revealed that VV2108 grouped with two other V. vulnificus strains isolated from humans. The pan-genome of V. vulnificus was constructed using 26 representative genomes to elucidate their genetic diversity, evolutionary characteristics, and virulence and antibiotic resistance profiles. The pan-genome analysis revealed that VV2018 shared a total of 3,016 core genes (≥ 99% presence), including 115 core virulence factors (VFs) and 5 core antibiotic resistance-related genes, and 309 soft core genes (≥ 95 and < 99% presence) with 25 other V. vulnificus strains. The varG gene might account for the cefazolin resistance, and comparative analysis of the genetic context of varG revealed that two genes upstream and downstream of varG were conserved. The glycosylation (pgl) like genes were found in VV2018 compared with Pgl-related proteins in Neisseria that might affect the adherence of the strain in hosts. The comparative analysis of VV2018 would contribute to a better understanding of the virulence and antibiotic resistance profiles of V. vulnificus. Meanwhile much work remains to be done to better understand the function of pgl-like genes in V. vulnificus.